Learning stick-figure models using nonparametric Bayesian priors over trees - Meeds, Ted; Ross, David A.; Zemel, Richard; Roweis, Sam (Conference on Computer Vision and Pattern Recognition (CVPR), 2008)
We present a probabilistic stick-figure model that uses a nonparametric Bayesian distribution over trees for its structure prior. Sticks are represented by nodes in a tree in such a way that their parameter distributions are probabilistically centered around their parent node. This prior enables the inference procedures to learn multiple explanations for motion-capture data, each of which could be trees of different depth and path lengths. Thus, the algorithm can automatically determine a reasonable distribution over the number of sticks in a given dataset and their hierarchical relationships. We provide experimental results on several motion-capture datasets, demonstrating the model’s ability to recover plausible stick-figure structure, and also the model’s robust behavior when faced with occlusion.